New approach towards imaging lambda-DNA using scanning tunneling microscopy/spectroscopy (STM/STS) - Dey, Shirshendu; Pethkar, Sushama; Adyanthaya, Suguna D.; Sastry, Murali; Dharmadhikari, C. V. (Bulletin of Materials Science, 2008)
A new methodology to anchor A-DNA to silanized n-Si(111) surface using Langmuir Blodget trough was developed. The n-Si (111) was silanized by treating it with low molecular weight octyltrichlorosilane in toluene. Scanning tunneling microscopy (STM) image of lambda-DNA on octyltrichlorosilane deposited Si substrate shows areas exhibiting arrayed structures of 700 nm length and 40 nm spacing. Scanning tunneling spectroscopy (STS) at different stages depict a broad distribution of defect states in the bandgap region of n-Si(111) which presumably facilitates tunneling through otherwise insulating DNA layer.
Keywords: DNA; Langmuir Blodget technique; Scanning tunneling microscopy; silanization

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

Effect of reduced particle size on the magnetic properties of chemically synthesized BiFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Here, we report the effect of reduction in particle size on the temperature dependent magnetization of chemically synthesized BiFeO3 nanocrystals with average grain size of 55 nm. The X-ray photoelectron spectroscopy results show a significant broadening of binding energy peaks associated to Fe3+ 2p(3/2) core levels due to the reduced size. Additionally, due to the nanosize effect, the M-H loops show a significant coercivity starting from 390 K with an anomaly located in the vicinity of 150 K in our H-c vs T as well as M-r/M-s(50 kOe) vs T curves. At this temperature, both H-c and M-r/M-s(50 kOe) undergo minima. Additionally, our results for the first time show the evidence of existence of a low temperature anomaly due to spin-glass transition in the range from 40-44 K in the field cooled magnetization curves. In bulk single crystals, this transition is reported to be situated at around 50 K, however, this transition remained so far undiscovered in the recent studies on BiFeO3 nanoparticles due to the insufficient temperature resolution. The significant shift in this transition toward lower temperature can be attributed to size dependent effects. Our results clearly present new information on the size dependent properties of BiFeO3 nanoparticles.

Magnetic and dielectric properties and Raman spectroscopy of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Maity, Tuhin; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2010)
The rare earth orthochromites are extremely interesting due to the richness of their optical, dielectric, and magnetic properties as well as due to their multiferroic properties which make them suitable materials to study in the nanoregime. However, the wet-chemical synthesis of these materials in nanosize is nontrivial. Here, we report for the first time, the detailed Raman spectra as well as magnetic and dielectric properties of chemically synthesized GdCrO3 nanoparticles of size ranging from 40 to 60 nm. The magnetic properties are dictated by competing Cr3+-Cr3+, Gd3+-Cr3+, and Gd3+-Gd3+ superexchange interactions in different temperature regions, resulting into an antiferromagnetic ordering at 167 K due to the Cr3+-Cr3+ followed by weak ferromagnetic ordering due to the onset of Cr3+-Gd3+ interactions. At lower temperature, it shows weak antiferromagnetic ordering due to Gd3+-Gd3+ interaction. Below 95 K, GdCrO3 nanoparticles showed the presence of negative magnetization due to Gd3+ and Cr3+ interactions resulting into weak ferromagnetic coupling. The Raman spectroscopy shows the characteristic Raman shifts indicating that below 450 cm(-1), Gd3+ ions play a dominant role in determining the phonon frequencies of GdCrO3, and above 450 cm(-1), the Cr+3 ions dominate. We also present for the first time the low temperature dielectric constant and loss tangent data for GdCrO3 in a broad temperature and frequency range. The dielectric constant shows a decrease in comparison to the bulk values due to the size dependent effects. It also shows a peak centered at around 320 K above which it shows a sharp decrease. The dielectric loss value in GdCrO3 nanoparticles is quite small and shows an interesting frequency dependent anomaly at lower temperature which might be due to the coupling between magnetic and dielectric order parameters.
Keywords: dielectric losses; gadolinium compounds; Magnetisation; Multiferroics; nanofabrication; Nanoparticles; permittivity; phonons; Raman spectra; superexchange interactions

Origin of magnetic anomalies below the neel temperature in nanocrystalline LuMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Rare earth manganites crystallize in distorted orthorhombic perovskite or hexagonal structures and exhibit quite interesting optical and magnetic properties dictated by the size of the rare earth ion. Many of these materials might exhibit both ferroelectric and magnetic ordering as well as magnetoelectric coupling. However, their physical properties at reduced particle sizes remain underexplored due to the challenges associated with their synthesis with a proper control over the crystalline phase. Here, we report the wet-chemical synthesis of the hexagonal phase of nanocrystalline LuMnO3 with an average crystallite size of similar to 32 nm. The room-temperature Raman spectroscopy data are consistent with the calculated values of isomorphous hexagonal RMnO3 (R = rare earth atom) compounds with P6(3)cm symmetry. The UV-vis-NIR spectra recorded in the diffused reflectance mode at room temperature show electronic transitions at 1.7 eV (729 nm), 2.3 eV (539 nm), and 5 eV (258 nm). The magnetization measurements show that the Neel temperature for the LuMnO3 is situated at around 89 K, which is in close proximity to the reported value of the bulk phase. We also observed two unique and field-dependent magnetic anomalies that were predicted earlier but never reported experimentally. The first anomaly is observed as a sharp bifurcation in the ZFC-FC curves below 44 K at a 100 Oe applied field, which is accompanied with a sudden rise in the coercivity and magnetization. A second transition is observed at 12 K as a sharp peak in the ZFC curves, which is accompanied with a dip in coercivity. We attribute the transition at 44 K to the reorientation of the Mn3+ ions due to the Dzyaloshinskii-Moriya interaction, and the transition at 12 K is explained by weak antiferromagnetic coupling between Mn-O-Mn in the ab plane, which becomes dominant at lower temperatures.

Temperature-dependent raman and dielectric spectroscopy of BiFeO3 nanoparticles: signatures of spin-phonon and magnetoelectric coupling - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Vivekanand, K.; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
We report the temperature-dependent Raman and dielectric spectroscopy of chemically synthesized BiFeO3 nanoparticles (average size similar to 50-60 nm). The Raman spectra (90-700 K) show two sets of transitions in the lowest Raman E mode, associated with Bi-O bond motion situated in close proximity to the spin reorientation transitions reported for BiFeO3, thereby indicating the existence of possible coupling between magnons and phonons for particle size below the helical order parameter (62 nm). These transitions are slightly shifted in temperature in comparison to the bulk single crystals. We also observe a step-like behavior in Raman peak position around the Neel temperature, suggesting that the phonons are influenced by the magnetic ordering in nanosized BiFeO3. The heat-flow measurements show two sharp endothermic peaks at 1094 and 1223 K representing rhombohedral to orthorhombic or monoclinic transition followed by transition into the cubic phase above 1200K. The low temperature (20-325 K), frequency-dependent (1-10(6) Hz) dielectric constant and loss tangent measurements show that the loss tangent (similar to 10(-3)) and ac conductivity values (similar to 10(-8) Ohm(-1)-cm(-1)) are orders of magnitude lower than the reported values for BiFeO3 ceramics, indicating high levels of ionic purity of our samples. The real part of the permittivity shows a slight reduction in its value (similar to 30) in comparison to the bulk single crystals. Similar to the Stokes Raman shift, its temperature-dependent dielectric constant also shows four weak anomalies at similar to 85, 168, 205, and 230 K situated in close proximity to the spin reorientation transitions, indicating magnetoelectric coupling.

Effect of particle size and annealing on spin and phonon behavior in TbMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2011)
Interest has grown to study TbMnO3 as it was recently reported to show a gigantic magnetoelectric effect. Here, we report the synthesis and detailed magnetic and Raman spectroscopy study on TbMnO3 particles of size similar to 25 nm and 2-3 mu m, respectively. The incommensurate-commensurate (lock-in) transition, usually observed at 27 K for bulk phase of TbMnO3 was not observed in susceptibility versus T curve but was seen at 30 K in the coercivity versus T curve in similar to 25 nm particles. This transition, which is due to the spin modulation length scale, gets weakened in nanosize due to the increased intrinsic lattice strain observed in 2-3 mu m particles, due to the effect of increased particle size. The increased value of magnetization in the 2-3 mu m sample was attributed to double exchange interactions between Mn+3 and Mn+4 spins. The role of annealing related effects on the fate of the Neel temperature for TbMnO3 was investigated. Raman spectroscopy indicated a decrease in the lattice distortion for similar to 25 nm particles. (c) 2011 American Institute of Physics. [doi:10.1063/1.3563571]

Surface effects on morin transition, exchange bias, and enchanced spin reorientation in chemically synthesized DyFeO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2011)
A giant linear magnetoelectric effect was observed by Y. Tokura's group recently in multiferroic DyFeO3, which demands a detailed investigation of its magnetic properties. Additionally, there is little information on the changes of chemical and physical properties of these materials with the reduction in particle size in spite of the potential applications of these materials nanoscale devices. As the wet-chemical synthesis of these materials in nanosize and getting a control over crystallinity and stoichiometry is nontrivial and poses a serious challenge prohibiting the study of their size-dependent properties. Here, we report the synthesis of DyFeO3 nanoparticles using a surfactantless hydrothermal method with a detailed magnetic property measurement. The as-synthesized DyFeO3 nanoparticles showed excellent crystallinitywith average particle size in the range 50-60 nm. The structural analysis indicated that they are of a distorted orthorhombic pervoslcite crystal structure. Detailed dc magnetization measurements in the temperature range of 3-350 K could isolate the presence of Dy3+-Fe3+ and Dy3+-Dy3+ superexchange interactions, which showed up as spin reorientation transitions in various temperature regions due to the differing magnitude of their interactions resulting in continuous rotation of antiferromagnetic component of Fe3+ spins with cooling of the sample. Nanosized DyFeO3 showed spin-reorientation transitions near 315 and 70K due to the Dy3+-Fe3+ interaction accompanied with an opening up of the hysteresis loop followed by antiferromagnetic ordering around 4 K due to a possible Dy3+-Dy3+ interaction. We also observed significant effect of the particle size reduction on the magnetic properties. The main effects seen. by us were in terms of (1) pronounced spontaneous spin reorientation transitions, (2) the absence of Morin transition, and (3) presence of temperature-dependent exchange bias in the DyFeO3 nanoparticles. We present a detailed mechanism to explain these features based on the interplay of Dy3+ and Fe3+ spins as well surface disorder, anisotropy, canting, and so forth.

Synthesis and optical studies of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Nanoparticle Research, 2011)
{Here we report for the first time, a detailed synthesis mechanism of GdCrO3 nanoparticles using a surfactant-less hydrothermal method. We also report a detailed study of their structural and optical properties. The selected area electron diffraction and powder X-ray diffraction studies of GdCrO3 nanoparticles show pure phase and excellent crystallinity with average particle size around 50-60 nm. The structural analysis indicates a distorted perovskite crystal structure with lattice parameter values of a = 5.3099 +/- A 0.0022
Keywords: hydrothermal; Nanoparticles; Rare earth orthochromites

Surface chemistry and growth mechanism of highly oriented, single crystalline TiO2 nanorods on transparent conducting oxide coated glass substrates - Sadhu, Subha; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (RSC Advances, 2013)
The fabrication of one-dimensional (1D) rods or wires of titania in desired crystalline facets is quite exciting due to unique optoelectronic properties. The single crystalline, oriented nanorods directly grown on transparent conducting oxide (TCO) substrates are finding a lot of interest in solar photovoltaics and several other optoelectronic devices due to enhanced electron transport and lower exciton recombination rates. However, the growth of desired crystalline facets of highly oriented, single crystalline nanorods on different substrates and understanding the interplay between the surface chemistry and growth mechanism still remain a non-trivial and challenging task. Here, for the first time, the kinetically controlled growth of the (310) facet of TiO2 nanorods on fluorine-doped tin oxide (FTO) coated glass substrate has been reported which is in contrast to the previously reported (002) faceted TiO2 nanorods. In addition to this, the growth of (110) facet TiO2 nanorods using amorphous fluorine doped silicon oxide (FSO) as a substrate is also demonstrated. In this paper, it is shown that two different faceted TiO2 nanorods can be synthesized following same synthetic condition by varying only the material properties of the substrate. To investigate the role of substrate chemistry on the morphology and single crystallinity of TiO2 nanorods, electron microscopy, XPS and contact angle measurements have been done. The results clearly indicate an important link between the surface chemistry and morphology of TiO2 nanorods. It can be assumed that there is a role of OH- and water groups which are responsible for the growth of plane (110) which has less surface energy. The observation of (310) facet is quite surprising and can be explained based on FTO crystallinity. It is possible to tune the diameter of the titania nanorods by further coating the FTO substrate with a thin gold layer due to increase in the hydrophilicity of the substrate. Finally, a light to electricity conversion efficiency of 2.5% could be achieved by using vertically grown titania nanorods on FTO as the photoanode in a dye sensitized solar cell (DSSC).